The Usage of New Multispectral Satellites in Agro-Environmental Protection - Takács, Péter; Tamás, János (Acta Agraria Debreceniensis, 2005)
GIS, and especially remote sensing, offers great help in performing agro-environmental protection tasks. It can process a large amount of data to an arranged set of databases, and is also an excellent source of information. Moreover its keeps the geographical coordinates of all data during processing. The usage of remotely-sensed data is one of the most up-to-date and effective ways to observe, analyze and understand the complex phenomena taking place in all the spheres of agricultural production (soil, water, air), and also to track and monitor the changes of different environmental parameters, as they constantly change in time and space. Several indices will be described, which can be derived from remote sensed data. Next, a relatively new hyperspectral satellite sensor (MODIS) will be introduced, as it can be a input data source in research performed in agri-environmental protection. Last, a new meteorological satellite (MSG-1) will be introduced, as its data are available for public usage, and it could be an important data source.